CAN THE PRIVATIZATION OF PRISONS SOLVE THE CRISIS OF THE PRISON SYSTEM IN PERU? - Espinoza Bonifaz, Augusto (2023)
This review article is dedicated, in the introduction, to describe the problems identified by the author regarding the prison system, as well as to determine its objectives. Then, it is exposed that the penal system, and not only its prison environment, has been wasting, for many years, the possibility that the custodial sentence fulfills its resocializing purpose. Subsequently, it explains what privatizing prison administration implies and what are the advantages and disadvantages of doing so. The Peruvian experience of productive prisons promoted since 2017 is described below. Finally, the main conclusions that have been reached as a result of the investigation are provided.